2021
DOI: 10.1186/s13002-021-00488-3
|View full text |Cite
|
Sign up to set email alerts
|

Shifting perceptions, preferences and practices in the African fruit trade: the case of African plum (Dacryodes edulis) in different cultural and urbanization contexts in Cameroon

Abstract: Background Understanding the perceptions, preferences and management practices associated with intraspecific variability of emblematic African tree crops is critical for their sustainable management. In this paper, we examine how the agrobiodiversity of a fruit tree species native to Central Africa, the African plum tree (Dacryodes edulis), is perceived and managed by Cameroonian cultivators. Methods Semi-structured interviews and tree surveys were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…Fruits’ morphology is one of the main traits of interest to farmers and consumers. It has been demonstrated that a large variation in shape, size, color and taste of the fruits exist in cultivation, as observed in our study and as already observed in previous studies [ 25 , 27 ] based on a larger sample size. The results obtained here support the hypothesis that the observed variation could be by human practices, with overall a tendency to select mostly individuals with bigger fruits.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Fruits’ morphology is one of the main traits of interest to farmers and consumers. It has been demonstrated that a large variation in shape, size, color and taste of the fruits exist in cultivation, as observed in our study and as already observed in previous studies [ 25 , 27 ] based on a larger sample size. The results obtained here support the hypothesis that the observed variation could be by human practices, with overall a tendency to select mostly individuals with bigger fruits.…”
Section: Discussionsupporting
confidence: 91%
“…Besides the size and the lipid content of the fruits, their taste is one of the main characters under selection. The fruits of cultivated D. edulis presented a great variation in sourness, and consumers’ preferences is usually for non-sour fruits [ 25 ]. The same variation seemed to exist in wild fruits (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress has been made during the third decade in the intraspecific characterization of Dacryodes edulis in Cameroon and Gabon [242,245,246,[291][292][293][294]; Irvingia spp. in Benin and Nigeria [233,[295][296][297]; G. kola in Nigeria [298][299][300][301][302], Cote d'Ivoire [303] and Benin [244,304,305]; Cola spp.…”
Section: Characterization Of Useful Traitsmentioning
confidence: 99%
“…Furthermore. perceptions of and preferences for fruit traits linked to intraspecifc tree diversity vary according to interethnic and rural-urban differences, which need to be considered in future domestication activities [246].…”
mentioning
confidence: 99%